2019
DOI: 10.11604/pamj.2019.33.326.18911
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis and HIV co-infection in Congolese children: risk factors of death

Abstract: IntroductionHuman immunodeficiency virus (HIV) and tuberculosis (TB) are the leading causes of death from infectious disease worldwide. The prevalence of HIV among children with TB in moderate to high prevalence countries ranges between 10% and 60%. This study aimed to determine the prevalence of HIV infection among children treated for TB in Directly Observed Treatment Short-Course (DOTS) clinics in Lubumbashi and to identify risk of death during this co-infection.MethodsThis is a cross-sectional study of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Poor completion of TB treatment among children aged 0-14 years at MRRH in Uganda was associated with HIV infection; three-quarters of patients with TB completed treatment, compared with only half of TB/HIV coinfected patients. Other studies in Democratic Republic of Congo, Ethiopia, Nigeria, Ghana and Vietnam have identi ed similar results [37][38][39][40][41][42]. There may be multiple factors that in uence this nding: HIV-infected patients may be more prone to depression, lowered family support, and reduced income, which could impact their treatment adherence [43].…”
Section: Discussionmentioning
confidence: 62%
“…Poor completion of TB treatment among children aged 0-14 years at MRRH in Uganda was associated with HIV infection; three-quarters of patients with TB completed treatment, compared with only half of TB/HIV coinfected patients. Other studies in Democratic Republic of Congo, Ethiopia, Nigeria, Ghana and Vietnam have identi ed similar results [37][38][39][40][41][42]. There may be multiple factors that in uence this nding: HIV-infected patients may be more prone to depression, lowered family support, and reduced income, which could impact their treatment adherence [43].…”
Section: Discussionmentioning
confidence: 62%
“…In fact, on previous multicenter observational research result indicated, infections other than TB contribute in one round infection 54-57 cells/mm3 substantially reduction of CD4 count[34]. Which directly favors reactivation of Mycobacterium tuberculosis bacilli to change active TB infections[21, 34,37]. In this study, not started isoniazid (INH) was significantly associated with the incidence of pulmonary tuberculosis.…”
mentioning
confidence: 60%
“…This exploratory analysis had limited power and did not determine a statistically significant difference in the case-fatality rate among the two populations. In published studies, TB manifestations have been shown to be more severe and progression to death more rapid among CLHIV compared to those living without HIV, with overall high rates of mortality, specifically amongCLHIV under the age five years [ 24 ] and in those with poor nutritional status [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%